The most - Anthony, Jessica, 1974- (Little, Brown and Company, 2024)
"It is an unseasonably warm Sunday in November 1957. Katheen, a college tennis champion turned Delaware housewife, decides not to join her flagrantly handsome life insurance salesman husband, Virgil, or their two young boys, at church. Instead, she takes a dip in the kidney-shaped swimming pool of their apartment complex. And then she won't come out. A consuming, single-sitting read set over the course of eight hours, The Most breaches the shimmering surface of a seemingly idyllic mid-century marriage, immersing us in the unspoken truth beneath. As Sputnik 2 orbits the earth carrying Laika, the doomed Soviet dog, Kathleen and Virgil hurtle towards each other until they arrive at a reckoning that will either shatter their marriage, or transform it, at last, into something real."--Provided by publisher.